Assessment of the rapid pullthrough technique in oesophageal manometry. Issue 2 (February 1980) - Goodall, R J; Hay, D J; Temple, J G
Abstract : The lower oesophageal sphincter pressure was measured by infusion manometry using the rapid pullthrough technique in two studies designed to evaluate this technique. The first study performed was an assessment of its reproducibility in individual subjects on separate occasions. We conclude that the rapid pullthrough technique does not give reproducible results. The second study compared the lower oesophageal sphincter pressure obtained by this technique with that by the standard station pullthrough technique. We conclude that the results are not comparable.